Perilaku Caring Perawat Mempengaruhi Kepatuhan Pasien Kanker dalam Menjalani Kemoterapi: Caring Behavior of Nurses Affects Cancer Patient's Compliance with Undergoing Chemotherapy - Trisnawati, Ina (Dohara POAJ, 2021)
Introduction: Adherence to undergo chemotherapy schedule was an urgent problem for cancer patients. We aimed to investigate the relationship between the nurse’s caring behavior and cancer patients' compliance in undergoing Chemotherapy. Methods: The study used a cross-sectional approach on 63 cancer patients who were undergoing chemotherapy, and used a total sampling technique. Data collection was performed using two questionnaires; the Caring Behaviour questionnaire adopted from Swanson (1991) and the Patient’s Compliance questionnaire adopted from Agustina (2015). Results: Nurses' caring behavior and cancer patients' compliance in undergoing chemotherapy had a significant relationship (p-value 0.000). Discussion: The caring behavior of nurses has an impact on the patients, increasing motivation for adherence to their chemotherapy schedule. Nurses should maintain their caring behavior, especially in the workplace at hospitals for patients with terminal illnesses. Caring will bring up a disciplined attitude in undergoing treatment, and growing the patient's personality to pay attention to their health.